Production of Processed Sago Porridge in Pemakuan Village Sungai Tabuk District - Irna Sari; Jumriani Jumriani; M. Ridha Ilhami; Sovia Husni Rahmia; Sigit Triyono (Journal of Social Development, 2026)
Randang porridge is a sago-based food product with high cultural value and potential as a local specialty product. Its production process requires skill and precision to achieve the desired taste and texture. However, information on the production process used is still very limited. The purpose of this study is to describe the production of randang porridge. This study uses a qualitative approach and descriptive method. Data collection techniques include observation, interviews, and documentation. For data analysis, the process involves data reduction, data presentation, and drawing conclusions. Data validity is confirmed through source triangulation, technique triangulation, and time triangulation. The research results show that one of the processed sago products produced in Pemakuan Village is randang porridge. The production process of sago porridge involves several stages, starting from sifting, granulation, roasting, and finally packaging. The tools used in the production process of bubur randang are still simple, such as gas stoves, pans, spatulas, sieves, cloth bags, and manual scales. Based on the research conducted, it was concluded that Pemakuan Village is known as one of the sago production areas in Sungai Tabuk Subdistrict, with many residents involved in sago processing as a livelihood. Sago-based products have high economic and nutritional potential, with sago being equivalent to or even higher in calories than other carbohydrates, making it a popular food and supporting increased local income. The processing process still employs simple and traditional technology, yet remains efficient and affordable.